2023
DOI: 10.3389/fpls.2023.1158837
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive monitoring of maize LAI by fusing UAV spectral and textural features

Abstract: Leaf area index (LAI) is an essential indicator for crop growth monitoring and yield prediction. Real-time, non-destructive, and accurate monitoring of crop LAI is of great significance for intelligent decision-making on crop fertilization, irrigation, as well as for predicting and warning grain productivity. This study aims to investigate the feasibility of using spectral and texture features from unmanned aerial vehicle (UAV) multispectral imagery combined with machine learning modeling methods to achieve ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…The correct timing of N application improves yield parameters, which increases grain yield [ 29 , 30 ]. However, improper optimisation of the rate and proportion of nitrogen application causes a number of problems in cultivation [ 31 ], slows growth rate, reduces grain yield and increases nitrogen loss, thereby affecting environmental quality [ 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The correct timing of N application improves yield parameters, which increases grain yield [ 29 , 30 ]. However, improper optimisation of the rate and proportion of nitrogen application causes a number of problems in cultivation [ 31 ], slows growth rate, reduces grain yield and increases nitrogen loss, thereby affecting environmental quality [ 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Features fusion strategy involve merging different types of features into a more optimal feature set, combining features with different features to construct models, and have the potential to mitigate the impact of spectral saturation effects, enhance model performance and increase the interpretability of prediction models (Zhou et al, 2022;Sun et al, 2023). This explains why the optimal SPAD estimation models in the late growth stage of winter wheat are constructed using features fusion strategy.…”
Section: The Impact Of Features Fusion Strategy On Spad Estimationmentioning
confidence: 99%
“…Val increased by 0.092 to 0.202, RMSE Val decreased by 0.076 to 4.916, and RPD Val increased by 0.237 to 0.960. Sun et al (2023) developed maize LAI estimation model using SVM, RF, BPNN, and PLSR algorithms by selecting five spectral features and three texture indices through correlation analysis. The results showed that the SVM algorithm with multi-variable fusion achieved the highest accuracy.…”
Section: The Impact Of Features Fusion Strategy On Spad Estimationmentioning
confidence: 99%
“…(celery) and Spinacia oleracea Linn. (spinach) and N. tabacum (tobacco) can be monitored using the sensors for high product yield ( Minervini et al., 2015 ; Jahnke et al., 2016 ; Minervini et al., 2017 ; Ubbens and Stavness, 2017 ; Zheng et al., 2019 ; Maimaitijiang et al., 2020 ; Fu et al., 2021 ; Sangjan et al., 2021 ; Sarkar et al., 2021 ; Yang et al., 2021a ; Banerjee et al., 2022 ; Bai et al., 2023a ; Bai et al., 2023b ; Sun et al., 2023 ). A detailed list of automation and AI-based tools used in plant monitoring is listed in Table 2 .…”
Section: Ai-based ML Algorithms In Recombinant Protein Productionmentioning
confidence: 99%